The Effectiveness of Generated Electrical Power Based on the Water Discharge of Reservoir - Rajagukguk, Antonius; Ervianto, Edy; Firdaus, Firdaus; Kusuma, Natasya Indra (International Journal of Electrical, Energy and Power System Engineering, 2024)
Renewable energy has an important role today, one of which is hydroelectric power plants which use water as the main resource. The operation of a hydroelectric power plant generally aims to maximize the water discharge available in the reservoir in order to obtain maximum energy generation. The main driver of hydropower development is the hydraulic turbines. It's a mechanical device that turns the potential energy of water into electrical energy. So researchers are interested in conducting research with the title analysis of the effectiveness of electrical energy based on reservoir conditions. The method used in this research is daily data collection in the form of reservoir elevation level data, outflow, and data on the electrical power generated by the generator. After that, calculate the water volume, hydraulic power, turbine mechanical power along with turbine efficiency, and the efficiency of the generator. Then analyze the values of hydraulic power, turbine mechanical power, electrical power based on water discharge over time. As well as analyzing the efficiency of the generator based on the electrical power that can be generated over a period of one year. Based on research, it is known that an increase in powerplant efficiency occurs after draining the reservoir with a value range of 70% - 72%, because mud deposits accumulate in the reservoir resulting in the reservoir water volume capacity not being optimal.